Korelasi Posisi Tip Catheter Double Lumen dengan Nilai Quick of Blood pada Pemasangan CDL Tunneling Vena Jugularis Interna Kanan di RSUP Prof. Dr. R. D. Kandou - Tubagus, Angga P.; Tjandra, Djony E.; Sumangkut, Richard (UNIVERSITAS SAM RATULANGI, 2019)
Abstract: Chronic kidney disease (CKD) is a global public health problem with increasing prevalence and incidence. Patients with CKD require kidney replacement therapy such as hemodialysis. The quick of blood (Qb) value is one of the most important determinants for adequate hemodialysis. Many factors can affect the Qb value, inter alia the catheter tip position. It is very complex and still controversial to determine the optimal position of the catheter itself. This study was aimed to determine the correlation between the double lumen catheter tip position and Qb value in insertion of the right internal jugular vein CDL tunneling at Prof. Dr. R. D. Kandou hospital. This was a correlation analytical study with a cross-sectional design. The position of the CDL tips were evaluated by using chest x-ray and the Qb values were determined by using hemodyalisis machine. Data were analyzed by using point-biserial correlation test. In total, 55 patients were included, mostly were males (56.4%) and late elderly (41.8%). The results showed that the average Qb value with CDL tip position in intraatrial (178.2 ml/minute) was slightly higher than the average Qb value with CDL tip position in CAJ (171.6 ml/minute). The bivariate analysis showed that the position of the double-lumen catheter tip had a weak positive correlation but not significant with the Qb value. Conclusion: There was a correlation but not statistically significant between the position of the CDL tip and the Qb value.Keywords: CKD, catheter tip position, catheter double-lumen, Quick of bloodAbstrak: Penyakit ginjal kronik (PGK) merupakan masalah kesehatan masyarakat global dengan prevalensi dan insidens yang terus meningkat. Pasien gagal ginjal memerlukan terapi pengganti ginjal seperti hemodialisis. Nilai quick of blood (Qb) merupakan salah satu penentu yang sangat penting bagi hemodialisis yang adekuat. Banyak faktor yang dapat memengaruhi nilai Qb, salah satunya ialah posisi tip kateter. Hal yang menentukan posisi optimal dari kateter sendiri sangat kompleks dan masih kontroversial. Penelitian ini bertujuan untuk mengetahui korelasi antara posisi tip kateter double lumen dengan nilai quick of blood pada pemasangan CDL vena jugularis interna kanan di RSUP Prof. Dr. R. D. Kandou Manado. Jenis penelitian ialah analitik korelasi dengan desain potong lintang. Alat ukur yang digunakan ialah foto toraks untuk menentukan posisi tip CDL dan mesin hemodialisa untuk melihat nilai Qb. Data hasil penelitian dianalisis dengan uji korelasi point-biserial. Subyek penelitian ini sebanyak 55 pasien, lebih banyak yang berjenis kelamin laki-laki (56,4%) dan berada dalam kategori usia lansia akhir (41,8%). Hasil penelitian menunjukkan nilai rerata Qb posisi tip CDL di intraatrial (178,2 ml/menit) sedikit lebih tinggi daripada rerata nilai Qb posisi tip CDL di CAJ (171,6 ml/menit). Hasil analisis data mendapatkan korelasi positif lemah dan tidak bermakna (antara posisi tip catheter double-lumen dengan nilai Qb. Simpulan: Terdapat korelasi yang tidak bermakna secara statistik antara posisi tip CDL dengan nilai Qb.Kata kunci: PGK, posisi tip kateter, double-lumen catheter, quick of blood